Precalculus (10th Edition)

Published by Pearson
ISBN 10: 0-32197-907-9
ISBN 13: 978-0-32197-907-0

Chapter 5 - Exponential and Logarithmic Functions - 5.3 Exponential Functions - 5.3 Assess Your Understanding - Page 280: 12



Work Step by Step

RECALL: (1) $\dfrac{1}{a^x} = a^{-x}$ (2) $(a^m)^n=a^{mn}$ Use rule (1) above to obtain: $\left(\dfrac{1}{3}\right)^x = \left(3^{-1}\right)^x$ Use rule (2) above to obtain: $\left(3^{-1}\right)^x = 3^{-1(x)} = 3^{-x}$ Note that $3^x \ne 3^{-x}$, so $y=3^x$ is not equivalent to $y=\left(\dfrac{1}{3}\right)^x$. This means that they have different graphs. Thus, the given statement is false.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.